Good Corporate Governance, Koneksi Politik, Leverage Terhadap Tax Avoidance Dengan Moderasi Corporate Social Responsibility - Fitriyana; Kamil, Krishna (Jurnal Akuntansi & Keuangan Unja, 2024)
This study aims to examine the influence of independent board of commissioners, audit committee, political connections, leverage on Corporate Tax Avoidance with moderation of corporate social responsibility disclosure. This study uses a quantitative method. The data analysis method used is a statistical analysis method using Eviews 12 software. The population of this study is manufacturing companies listed on the IDX with a total of 56 companies that meet the sample selection criteria. The results of this study indicate that the independent board of commissioners (DKI) has a positive effect on Corporate Tax Avoidance (CTA). the audit committee (KA) has a negative effect on Corporate Tax Avoidance (CTA). political connections (KP) have no effect on Corporate Tax Avoidance (CTA). leverage (Lev) has a negative effect on Corporate Tax Avoidance (CTA). CSR is unable to moderate the influence of the independent board of commissioners on Corporate Tax Avoidance. CSR weakens the influence of the audit committee on Corporate Tax Avoidance. that CSR is unable to moderate the influence of political connections on Corporate Tax Avoidance. CSR is unable to moderate the influence of leverage on Corporate Tax Avoidance.